2020
DOI: 10.1016/j.chest.2020.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Fatal Outcome in Hospitalized Subjects With Coronavirus Disease 2019 From a Nationwide Analysis in China

Abstract: BACKGROUND:The novel coronavirus disease 2019 (COVID-19) has become a global health emergency. The cumulative number of new confirmed cases and deaths are still increasing out of China. Independent predicted factors associated with fatal outcomes remain uncertain.RESEARCH QUESTION: The goal of the current study was to investigate the potential risk factors associated with fatal outcomes from COVID-19 through a multivariate Cox regression analysis and a nomogram model. STUDY DESIGN AND METHODS:A retrospective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

75
534
11
25

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 566 publications
(666 citation statements)
references
References 22 publications
(27 reference statements)
75
534
11
25
Order By: Relevance
“…In accordance with previous studies on severe acute respiratory syndrome (SARS) [11], Middle East respiratory syndrome (MERS) [12] and COVID-19 [13], older age was also identi ed as a predictor for poor prognosis of patients with COVID-19 in our study. It is hypothesized that immunosenescence and/or underlying comorbidities might deem geriatric patients more vulnerable to developing severe COVID-19 illness.…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with previous studies on severe acute respiratory syndrome (SARS) [11], Middle East respiratory syndrome (MERS) [12] and COVID-19 [13], older age was also identi ed as a predictor for poor prognosis of patients with COVID-19 in our study. It is hypothesized that immunosenescence and/or underlying comorbidities might deem geriatric patients more vulnerable to developing severe COVID-19 illness.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies reported non-survivors present a higher proportion of various co-existing chronic illnesses in univariate analysis [4,[10][11][12]. Consistent with previous reports [10,13,14], our study indicated that COVID-19 patients with heart, liver, and kidney comorbidities had a higher risk of related organ injuries and death, compared with those without comorbidities. The cardiac, liver, and kidney complications can occur precipitously at any point during hospitalization and are increasingly being described as late complications that can occur after improvements in a patient's respiratory status.…”
Section: Discussionsupporting
confidence: 90%
“…variables) that ML can better utilize to represent the problem/target outcome, (2) feature selection, applying expert domain knowledge, statistical methods, and/or ML methods to remove 'irrelevant' features from consideration and improve downstream modeling, (3) data harmonization, allowing for the integration of data collected at different sites/institutions, (4) handling different outcomes and related challenges, e.g. binary classification, multi-class, quantitative phenotypes, class imbalance, temporal data, multi-labeled data, censored data, and the use of appropriate evaluation metrics, (5) ML algorithm selection for a given problem can be a challenge in itself, thus strategies to integrate the predictions of multiple machine learners as an ensemble are likely to be important, (6) ML modeling pipeline assembly, including critical considerations such as hyper-parameter optimization, accounting for overfitting, and clinical interpretability of trained models, and (7) considering and accounting for covariates as well as sources of bias in data collection, study design, and application of ML tools in order to avoid drawing conclusions based on spurious correlations.…”
Section: Advanced Computational Approaches To Diagnosis Decision Makmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID-19) pandemic has had a significant impact on population health and wellbeing. Research efforts are underway to identify vaccines [1], improve testing [2,3], understand transmission [4], develop serologic tests [5], develop therapies [6], predict risk [7], and develop mitigation and prevention strategies [8,9]. Biomedical informatics is central to each of these research efforts and for the delivery of healthcare for COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%